La partecipazione politica dei migranti. Dall’esclusione alle diverse forme di mobilitazione - Lotto, Marta (SocietàMutamentoPolitica, 2015)
The aim of this contribution is to develop several lines of investigations on the subject of political participation of migrants, namely: the possible heuristic value deriving from the understanding of migrants as a category, the connection between political participation and exclusion and the plurality of ways in which migrants actively express themselves.